Fuzzy and Taguchi based Fuzzy Optimization of Performance Criteria of the Process Control Systems - Kara, Fatih; Kucuk, Arda; Simsek, Baris (International Journal of Intelligent Systems and Applications in Engineering, 2018)
This paper proposes a Taguchi based Fuzzy and Fuzzy PID application using MATLABÂ® version 2015a to assess and optimize of process control performance criteria of liquid level and flow rate control system. When the main effect graphs for the liquid level and flow rate control system are evaluated, it was seen that the change in the membership function is the most effective factor on the process control performance. It can be said that the Gaussian membership function provides the lowest mean and standard deviation in the offset value. Improvement rates for âovershootâ, ârise timeâ, âfirst peak timeâ, â%95 setting time, â%99 setting timeâ, âmeanâ and âthe standard deviation of the offset valuesâ are %50, %50, %55, %77, %64, %5, %63 for flow rate control system; %50, %49, %55, %43, %48, %4, %63 for liquid level control system in order. In comparison with the classical PID method, in the Fuzzy PID method, the improvement is calculated as 54% in the average of the offset value and 99% in the standard deviation.